Uncovering the embodied dimension of the wandering mind - Leah Banellis; Niia Nikolova; Malthe Brændholdt; Melina Vejlø; Ignacio Rebollo; Nicolas Legrand; Francesca Fardo; Jonathan Smallwood; Micah G. Allen (Proceedings of the National Academy of Sciences, 2026)
When at rest, the mind becomes preoccupied with self-generated thoughts, commonly known as mind-wandering. While the social, autobiographical, and temporal features of these thoughts have been extensively studied, little is known about how frequently the wandering mind turns toward the interoceptive and somatic body. To map this underexplored component of “body-wandering,” we conducted a large-scale neuroimaging study in 536 healthy participants, expanding a retrospective multidimensional experience sampling approach to include probes targeting visceral and somatomotor thoughts. Our findings reveal a robust interindividual dimension of body-wandering characterized by negative affect, high autonomic arousal, and a reduction in socially oriented thoughts. Despite this negative tone, individual differences in the propensity for body-wandering thoughts were associated with lower self-reported symptoms of ADHD and depression. Multivariate functional connectivity analyses further revealed that affective, body-oriented thoughts are related to a pattern of thalamocortical connectivity interlinking somatomotor and interoceptive-allostatic cortical networks. Collectively, these results demonstrate that self-generated thoughts exhibit core embodied features which are linked to the ongoing physical and emotional milieu of the visceral body.